(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Assessing the poverty reduction in terms of food subsidies through Public Distribution System (PDS) is an important means by which the income transfer between poor and rich expenditure classes can be analyzed. The study intends to analyze the impact of PDS on poverty and Food security in rural and urban areas. The Public Distribution System (PDS) evolved as a system of management of scarcity through distribution of food grains at affordable prices. Over the years, PDS has become an important part of Government’s policy for management of food economy in the country. The Public Distribution System (PDS) of India plays a crucial role in reducing food insecurity by acting as a safety net by distributing essentials at a subsidised rate. While the PDS forms a cornerstone of government food and nutrition policy, India continues to be home to a large population of hungry and malnourished people. This review seeks to explore the functioning and efficiency of the PDS in achieving food and nutritional security in India. The PDS has the potential to act as a solution to food insecurity in India if the operational inefficiencies and environmental footprints are addressed by adequate policy reforms. Food security for a country meant sufficient quantity of essential commodities produced, stored properly and made available to all of the people at all times, especially the under privileged sections. The present article will discuss the role of public distribution system in addressing poverty and food security in the country.